Three‐dimensional configuration of orientated fibers as guidance structures for cell migration and axonal growth. Issue 2 (16th September 2013) - Kriebel, Andreas; Rumman, Muhammad; Scheld, Miriam; Hodde, Dorothee; Brook, Gary; Mey, Jörg
Abstract Peripheral nerve injuries can be surgically repaired by suturing the transected nerve stumps or, in case of larger lesions, by the transplantation of an autologous nerve graft. To avoid donor site morbidity, the development of artificial implants is desired. Clinically, hollow conduits have been used for this purpose but are inferior to the autograft because they lack internal guidance cues for Schwann cells and regenerating axons. In this article, we describe the design of a three‐dimensional (3D) scaffold consisting of parallel fibers embedded in a collagen matrix. For this purpose, an electrospinning device was developed to produce and manipulate a 3D array of aligned poly(ɛ‐caprolactone) (PCL) microfibers. This fiber array was then incorporated into biodegradable PCL tubes to serve as artificial nerve bridges. Using primary cultures of embryonic chicken dorsal root ganglia, we show that PCL microfibers in the 3D matrix of our composite scaffold guide the direction of Schwann cell migration and axonal growth. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 356–365, 2014.